1968
DOI: 10.1021/jm00309a010
|View full text |Cite
|
Sign up to set email alerts
|

3-Substituted 1,4-benzodiazepin-2-ones

Abstract: The preparation of a number of 1,4-benzodiazepines substituted in the 3 position is described. The rearrangement of 7-chloro-l,3-dihydro-5-phenyl-2H-l,4-benzodiazepin-2-one 4-oxide with diacetyl sulfide yields largely the 3-acetylthio compound. Amines, ethers, and sulfides were prepared through the chloro intermediate. A 3-carbethoxybenzodiazepine was prepared and converted into oxazepam. The pharmacological test data of new and previously published compounds are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…3-Alkyl and 3-amido substituents are reported (23,(32)(33)(34)40) to be detrimental to anti-anxiety activity. Our results are consistent with these reports.…”
Section: Resultsmentioning
confidence: 99%
“…3-Alkyl and 3-amido substituents are reported (23,(32)(33)(34)40) to be detrimental to anti-anxiety activity. Our results are consistent with these reports.…”
Section: Resultsmentioning
confidence: 99%
“…When an excess of chloroacetyl chloride was used, an additional product, XVI (derived from diacylation), was obtained. When the analogous N -oxide rearrangement of XV with methyl chloroformate was carried out, a mixture of the carbonate XVII and the chloro Compound XVIII (1) was obtained. The carbonate, uncontaminated with XVIII, could be prepared from the 3-hydroxy Compound I1 upon treatment with methyl chloroformate.…”
Section: And Discussionmentioning
confidence: 99%
“…Recent efforts (1) in the area of 3-hydroxy-1,4-benzodiazepines have been directed to the preparation of water-soluble derivatives suitable for parenteral administration. Aqueous 1,4-benzodiazepine solutions would be expected to have the distinct advantage of diminishing the incidence of pain and the subsequent venous inflammation often encountered with injectable formulations of water-insoluble 1,4-benzodiaze pines.…”
mentioning
confidence: 99%
“…Since the reaction rate of MeOX in EtOH was higher than that of EtOX in MeOH, the results in Figures 4 and 5 (numerical values in Table 1) suggested that the nucleophilicity of the leaving nucleophile played a more important role than that of the attacking nucleophile in determining the reaction rates. A more definitive answer regarding the relative contribution of nucleophilicity of attacking and leaving nucleophiles on the acid-catalyzed heteronucleophilic substitution reaction rate may be obtained by (1) comparing reaction rates of a 3-akoxy-1,4-benzodiazepine in a series of alcohols such as methanol, ethanol, n-propanol, n-butanol, and n-pentanol, and (2) comparing reaction rates of several different 3-akoxy-1,4-benzodiazepines (such as MeOX, EtOX, 3-0-n-propoxyoxazepam, 3-O-n-butoxyoxazepam, and 3-0-n-pentoxyoxazepam) in a single alcoholic solvent. These studies are being planned in our laboratory.…”
Section: Thermodgnamic Parameters and Isotope Effectmentioning
confidence: 99%